Organization of the educational process in the Rural School of the mountain region: a case study - Olena Budnyk; Inna Nikolaesku; Nataliia Stepanova; Olena Vovk; Anna Palienko; Tetiana Atroshchenko (Universidade Federal do Norte do Tocantins, 2021)
The purpose of the article is to present the problems of a typical rural school in a mountainous region in terms of the organization of the educational process, in particular distance learning of students in a coronary virus pandemic. The following research methods were used: analytic-synthetic, empirical and mathematical statistics. The specifics of the organization of schoolchildren's education in the alpine conditions of a small rural school are substantiated. The results of an empirical study conducted among teachers of rural schools in the mountains of Ukraine are presented. The subject of the survey were questions about the attitude of teachers to distance learning in rural schools, the realities and difficulties of using information and communication technologies (ICT) in the educational process. It was found that among teachers of various levels of rural education (preschool, primary and secondary school) 49.12% have a positive attitude to distance learning, 18.42% - partially support. Given the difficulties and problems of using ICT, lack of teaching materials for online learning, low level of digital and media literacy, 23.68% of teachers - strongly against this form of organization of the educational process in remote rural (mountainous) regions. Prospects for the development of rural schools in mountainous areas in the context of digitalization of education are identified.